The burden of mental disorders, substance use disorders and self-harm among young people in Europe, 1990–2019: findings from the Global Burden of Disease Study 2019 - Castelpietra, G; Knudsen, AKS; Agardh, EE; Armocida, B; Beghi, M; Iburg, KM; Logroscino, G; Ma, R; Starace, F; Steel, N; Addolorato, G; Andrei, CL; et al. (Elsevier, 2022)
Background Mental health is a public health issue for European young people, with great heterogeneity in resource allocation. Representative population-based studies are needed. The Global Burden of Disease (GBD) Study 2019 provides internationally comparable information on trends in the health status of populations and changes in the leading causes of disease burden over time.